Cosine fitting radiography and computed tomography - 李盼云 张凯 黄万霞 袁清习 王研 鞠在强 吴自玉 朱佩平 (Chinese physics B, 2015)
A new method in diffraction-enhanced imaging computed tomography （DEI-CT） that follows the idea developed by Chapman et al. [Chapman D, Thomlinson W, Johnston R E, Washburn D, Pisano E, Gmur N, Zhong Z, Menk R, Arfelli F and Sayers D 1997 Phys. Med. BioL 42 2015] in 1997 is proposed in this paper. Merged with a ＂reverse projections＂ algorithm, only two sets of projection datasets at two defined orientations of the analyzer crystal are needed to reconstruct the linear absorption coefficient, the decrement of the real part of the refractive index and the linear scattering coefficient of the sample. Not only does this method reduce the delivered dose to the sample without degrading the image quality, but, compared with the existing DEI-CT approaches, it simplifies data-acquisition procedures. Experimental results confirm the reliability of this new method for DEI-CT applications.